Phase space methods for non-linear analysis of pedalling forces in cycling - Kunert, A.; Ott, M.; Reuter, T.; Koska, D.; Maiwald, C. (PLOS ONE, 2018)
From the perspective of dynamic systems theory, stability and variability of biological signals are both understood as a functional adaptation to variable environmental conditions. In the present study, we examined whether this theoretical perspective is applicable to the pedalling movement in cycling. Non-linear measures were applied to analyse pedalling forces with varying levels of subjective load. Materials and methods